Targeting the P2X7 receptor in cerebrovascular diseases: from molecular mechanisms to preclinical therapeutic potential - Hu, Ziyan; Xie, Shujing; Chen, Cheng; Luo, Zhihui; Deng, Xiao; Xiao, Renjie (Frontiers in Pharmacology, 2025)
Cerebrovascular diseases seriously damage human health and impose a huge burden on society. Research on the mechanisms of cerebrovascular disease occurrence and development is of great significance in preventing the occurrence of the disease and improving the quality of life of patients. P2X7 Receptor (P2X7R), as a non-selective cation channel of the purinergic receptor family, is considered to be expressed in various immune cells within the nervous system and may also be expressed in neurons. Recent studies have identified P2X7R as a significant player in the progression of cerebrovascular diseases, potentially linked to its role in regulating neuroinflammation, cellular autophagy, and vascular function. This review elucidates the biological foundation of P2X7R, compiles various molecular mechanisms associated with cerebrovascular diseases, emphasizes recent research on the involvement of P2X7R in the pathogenesis of cerebrovascular diseases, and assesses the pharmacological implications of P2X7R in these conditions. By exploring the connections between P2X7R and cerebrovascular diseases, the therapeutic potential of targeting P2X7R in these conditions can be assessed, ultimately paving the way for novel therapeutic strategies to ameliorate the impact of cerebrovascular diseases.